Pengembangan Kerjasama Sub-Regional BIMP-EAGA Di Bidang Ekowisata: Perspektif Indonesia - Devy Putri Kussanti (Universitas Bina Sarana Informatika, 2017)
ABSTRACT BIMP-EAGA cooperation is a realization of regionalism institutions in the form of regional/sub-regional to reach the interest of economy, particularly trade, investment and tourism. One of the benefits of sub-regional cooperation, including the BIMP-EAGA is among the factors of geographical proximity of countries members. In the context of the tourism development the stakeholders in this BIMP-EAGA cooperation can take the advantage of this geographical factors, in addition, they also can take the benefits in other forms such as wealth in natural and beauty resources, the diverse of cultural, including traditional community property. The BIMP-EAGA cooperation wants to develop the ecotourism concept or community-based ecotourism as a blend between the tourism sector, the environment (friendly environment) and the economic sector, namely, the empowerment of the local communities in the ecotourism management can increase their income and welfare through the development of Small and Medium Enterprises (SMEs). As a facilitator, Indonesian government has a big role to provide the primary and supporting facilities associated with the availability of adequate physical infrastructure and regulatory and the policy in the ecotourism. The benefits of ecotourism of developmental in Indonesia is to create good image of Indonesian politics in terms of nature conservations property and the environment, especially in preventing or tackling the worse impact of global warming and climate change. Keywords: BIMP-EAGA Cooperation, Ecotourism, Indonesia. ABSTRAK Kerjasama BIMP-EAGA merupakan sebuah realisasi dari regionalisme dalam bentuk institusi regional/sub-regional untuk mencapai kepentingan ekonomi, khususnya perdagangan, investasi dan pariwisata. Salah satu keunggulan kerjasama sub-regional adalah faktor kedekatan geografis antar wilayah negara-negara anggotanya. Dalam konteks kerjasama pariwisata BIMP-EAGA, para pemangku kepentingan pun memanfaatkan faktor geografis ini, selain juga keunggulan yang lain berupa kekayaan dan keindahan sumber daya alam, keragaman budaya daerah, termasuk budaya tradisional masyarakatnya.Kerjasama BIMP-EAGA di bidang pariwisata ingin mengembangkan konsep ekowisata atau community based ecotourism sebagai konsep yang memadukan sektor pariwisata, lingkungan hidup dan sektor ekonomi atau pemberdayaan ekonomi masyarakat lokal. Keikutsertaan masyarakat lokal dalam pengelolaan ekowisata dapat meningkatkan kesejahteraan dan pendapatan mereka melalui pengembangan usaha kecil dan menengah (UKM). Sebagai fasilitator, pemerintah Indonesia berperan besar untuk menyediakan fasilitas utama maupun pendukung yang berkaitan dengan ketersediaan infrastruktur fisik serta regulasi dan kebijakan di bidang ekowisata. Selain keuntungan ekonomi, bagi Indonesia pengembangan ekowisata dapat membentuk citra politik Indonesia dalam upaya pelestarian alam dan lingkungan hidup secara global terutama dalam mencegah dan menanggulangi dampak lebih buruk dari global warming dan climate change. Kata Kunci: Kerjasama Sub-regional BIMP-EAGA, Ekowisata, Indonesia.